RANCANG BANGUN ALAT PEMOTONG DAUN BAWANG BERBASIS INTERNET OF THINGS (IOT) - Maharani, Luftya; Sarjana, Sarjana; Zefi, Suzan (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The utilization of Internet of Things (IoT) technology in the agriculture sector continues to evolve, including in the automation of agricultural processing tools. This research aims to design and develop an IoT-based scallion cutting tool integrated with the Blynk application, which functions to control and manage the device in real-time. This tool is equipped with key components such as a cutting motor, sensors, and a microcontroller, all controlled via the IoT network. The Blynk application allows users to adjust cutting parameters, such as motor speed, and receive information about the tool's status. Testing has shown that this tool can operate automatically according to settings provided through the Blynk app, producing consistent scallion cuts that meet the requirements. The implementation of this technology is expected to enhance efficiency, reduce manual labor and time, and improve the productivity and quality of scallion cutting. With the integration of IoT and the Blynk application, this scallion cutting tool offers an innovative solution to support the modernization of the agricultural industry, particularly in scallion processin.